2010
DOI: 10.2460/ajvr.71.7.755
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macrostructural and microstructural bone features in Thoroughbred racehorses with and without midbody fracture of the proximal sesamoid bone

Abstract: Fractured PSBs had adapted to high loading but had focal evidence of excessive remodeling and porosity that likely predisposed the horses to complete fracture and catastrophic injury. Detection of focal injury before complete fracture provides an opportunity for prevention of catastrophic injury. Development of diagnostic imaging methods to assess porosity of PSBs may help to identify at-risk horses and allow for modifications of training and racing schedules to reduce the incidence of PSB fracture in Thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
82
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 23 publications
13
82
2
Order By: Relevance
“…10,14,15 Histologic evaluation has identified structural changes in the PSBs of trained versus untrained Thoroughbreds. 16,17 Results of a study 17 in which histomorphometric analysis was used to evaluate the PSBs indi- …”
mentioning
confidence: 99%
“…10,14,15 Histologic evaluation has identified structural changes in the PSBs of trained versus untrained Thoroughbreds. 16,17 Results of a study 17 in which histomorphometric analysis was used to evaluate the PSBs indi- …”
mentioning
confidence: 99%
“…Comminuted proximal sesamoid fractures were the most common configuration in the current study (58%; 14/24), while American studies reported mid-body (Anthenill, Gardner et al 2010) and basilar fractures (Parente, Richardson et al 1993) being more common. Alternatively, fractures of the carpal bones, first phalanx and third metacarpal bone were largely noncatastrophic.…”
Section: Discussionmentioning
confidence: 42%
“…Calcein labels highlighting active osteonal bone formation was mainly seen towards the dorsal epiphysis, suggesting that modelling occurred towards the cancellous regions of the condyle in horses in the training group rather than an increase in size (Boyde and Firth 2005). Bone modelling towards cancellous bone regions was also seen in another experimental study of proximal sesamoid bones, with microradiography showing densely compacted cancellous bone in both the proximal sesamoid fracture and non-proximal sesamoid fracture groups (Anthenill, Gardner et al 2010). Similar to earlier in vitro bone studies discussed earlier, these studies reduced confounding by restriction or matching to gender, breed and age (Boyde and Firth 2005, Davies 2005, Davies 2006, Anthenill, Gardner et al 2010.…”
Section: Adaptation Through Bone Modellingmentioning
confidence: 62%
See 2 more Smart Citations